Children's rights and the regulations on the transfer of young players in football. (February 2020) - Yilmaz, Serhat; Esson, James; Darby, Paul; Drywood, Eleanor; Mason, Carolynne
Children who interact with football's recruitment and transfer processes encounter a complex web of regulations and practices. Debates over how to ensure that the interests and well-being of young football players are adequately protected, and that risks to their rights and welfare are identified and addressed, have become a topic of academic, political and media concern. This commentary article provides an overview of the Fédération Internationale de Football Association (FIFA) regulations concerning the mobility and representation of minors in player recruitment processes, in particular the Regulations on the Status and Transfer of Players and the Regulations on Working with Intermediaries. We examine these regulations through the lens of the United Nations Children's Rights Conventions (UNCRC). In so doing, the article demonstrates how football's regulatory frameworks and commercial practices inadvertently yield consequences that operate against the best interests of children involved in the sport. To counteract this, it is proposed that all planning, implementation, monitoring and evaluation of regulations involving the recruitment and transfer of young people should be explicitly informed by globally accepted standards of children's rights, such as the UNCRC. More specifically, it is argued that FIFA should adopt an approach that places the child at the centre of regulatory frameworks and characterises the child as a 'rights holder'.